Optimizing the Patriot Team Patrol in Preventing the Crime of Motor Vehicle Theft in the Legal Territory of the Bekasi City Police Metro - Abda Farreldaffa (Police Studies Review, 2021)
This research is motivated by the case of motor vehicle theft in the city of Bekasi which never decreases from year to year and even increases every year. This study aims to determine the implementation of patrols by the Patriot team in preventing motor vehicle theft, the factors that influence the implementation of patrols by the patriot team, and efforts to optimize patrols by the patriot team of Polres Metro Bekasi City. This research was conducted using a qualitative approach, using conceptual literature and using field research methods, namely field research, as well as data collection by interviews, observations, and document studies. Of course, from this research, it can be seen clearly the description of the patrols carried out by the Patriot team to prevent the crime of motor vehicle theft in the jurisdiction of the Bekasi City Police Metro. The results of the study found that the implementation of patrol activities by the patriot team was still not optimal because the crime of motor vehicle theft was still increasing from year to year. This is influenced by internal and external factors, including patrol personnel who do not meet the standards, there are damaged facilities and infrastructure, there is no special budget for the patriot team provided by the Polres, while external factors are very wide within the jurisdiction of the Bekasi Metro Police. Based on the results of the study, the researchers suggest to improve the quality of the Patriot team personnel, immediately establish a patriot team organizational structure, provide a special budget for the patriot team by the Bekasi City Police, there must be officers attached to the patriot team specifically, not just pickets.